2021
DOI: 10.1007/978-3-030-77772-2_15
|View full text |Cite
|
Sign up to set email alerts
|

Putting a Face on Algorithms: Personas for Modeling Artificial Intelligence

Abstract: We propose a new type of personas, artificial intelligence (AI) personas, as a tool for designing systems consisting of both human and AI agents. Personas are commonly used in design practices for modelling users. We argue that the personification of AI agents can help multidisciplinary teams in understanding and designing systems that include AI agents. We propose a process for creating AI personas and the properties they should include, and report on our first experience using them. The case we selected for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
(43 reference statements)
1
0
0
Order By: Relevance
“…This observation is consistent with the findings of Karahasanović et al (2021), who found that the lack of perceived humanity in AI applications can lead to mistrust and discomfort. Furthermore, the quote also illustrates the frustration caused by a failed interaction with AI.…”
Section: User-friendliness: Lack Of Humanity and Disappointing Experi...supporting
confidence: 92%
“…This observation is consistent with the findings of Karahasanović et al (2021), who found that the lack of perceived humanity in AI applications can lead to mistrust and discomfort. Furthermore, the quote also illustrates the frustration caused by a failed interaction with AI.…”
Section: User-friendliness: Lack Of Humanity and Disappointing Experi...supporting
confidence: 92%